Economic Growth And Carbon Dioxide Emissions: The Environmental Kuznets Curve Hypothesis In Yemen (المجلة العراقية للعلوم الاقتصادية, 2022)
AbstractThis study investigates the validity of the Environmental Kuznets Curve hypothesis in Yemen and the causal relationships between Carbon dioxide emissions, per capita income, energy consumption, trade openness, and industrial share to GDP. ARDL bounds testing approach to cointegration, Error Correction Model, and Toda-Yamamoto procedure to Granger causality techniques were employed on annual data covering the period from 1990 to 2010. long run relationship between CO2 emissions and its determinants with significant effects for per capita GDP and trade openness, whereas, energy consumption and trade openness appear to be important determinants of CO2 emissions in the short run. Besides, based on Narayan and Narayan (2010) approach, it is found that the EKC hypothesis does not hold in Yemen and therefore the effect of per capita income on CO2 emissions is monotonically increasing. Toda-Yamamoto causality test proved the existence of bidirectional causal relationships between economic growth and CO2 emissions, between energy consumption and economic growth, and between trade openness and energy consumption.